SERVICES FOR PERSONS WITH DISABILITIES (STUDY AT THE OFFICE OF THE POPULATION AND CIVIL REGISTRY OFFICE OF ENREKANG REGENCY) - Yamin, Muh Nur; Hairia, Hairia; Sakawati, Herlina; Fitri, Anisa (Universitas Negeri Makassar, 2024)
This study aims to evaluate the quality of services provided by the Enrekang Regency Population and Civil Registration Office to people with disabilities to the facilities and services available in the office. This research includes qualitative descriptive research with data collection techniques through Observation, Interviews and Documentation. The Miles and Huberman Data Analysis technique consists of data condensation, data presentation, and conclusion drawn.The results of this study show that the Services for Persons with Disabilities in the Population and Civil Registration Office of Enrekang Regency in general have not been fully successful from six (6) service evaluation indicators, namely Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. The Effectiveness indicator shows that it has not been running well, it is seen from the availability of facilities and accessibility for people with disabilities in accessing services such as the unavailability of special toilets for people with disabilities, special parking and information related to service procedures for people with disabilities so that it has not been said to be optimal. Efficiency shows that it has not gone well because in the process of recording ID cards which are carried out outside the scope of the Enrekang Regency Population and Civil Registration Office (pick up the ball), recording facilities such as cameras are still lacking, making this an obstacle during the process of picking up the ball. The adequacy shows that human resources (HR) can be said to be sufficient in providing services to the community, but the resources for infrastructure provided by the Enrekang Regency Population and Civil Registration Office that are needed by people with disabilities in the administrative service process are still inadequate. Equity shows that there is a separate policy given to people with disabilities in making it easier to access public services and also in the decision-making process, the Population and Civil Registration Office of Enrekang Regency consults with people with disabilities to obtain advice and input on how to provide accessibility and good services. Responsiveness shows that the Enrekang Regency Population and Civil Registration Office has implemented the correct public service system where officers as quickly as possible respond and respond to complaints and obstacles from the community during service. The accuracy shows that people with disabilities have felt the positive impact of the services provided, where they can feel that their rights have been fulfilled in receiving services according to the needs of people with disabilities. Of the six (6) service indicators, there are three (3) service indicators that have not been maximized, so it needs to be optimized again to improve quality services for people with disabilities.